FEATURES OF THE FUNCTIONING OF PRODUCTION RESOURCE MARKETS - KRAVETS, Iryna (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article is devoted to the issue of the functioning of markets for production resources. The essence of the market as a complex and multifaceted phenomenon is revealed, which is a set of relations associated with the purchase and sale of goods and services. Market relations are regulated by the ratio of demand and supply, as well as the method of interaction between producers and consumers, which is based on the price component. The market is an intermediate link between production and consumption and the sphere of entrepreneurial activity. The possibilities of enterprises to achieve economic goals are resource-limited in physical, economic and legal aspects. A market system is a set of interconnected markets that cover various areas of human activity. The commodity market functions through the interaction of producers, traders, and consumers through the determination of the price of raw materials that underpin the global economy. A resource used to produce a certain amount of economic goods for profit is capital, which exists in various forms: material (physical capital) and monetary (financial capital). The demand for capital, as for any factor of production, depends on its marginal profitability. Land as a factor of production differs from capital in that it does not have the ability to reproduce. The legal basis for the creation of a land market was laid by the adoption of the new Land Code in Ukraine. The labor market is a specific commodity market, one of the most complex, as it encompasses not only the goods offered, but also a whole complex of social and labor relations, the quality of which will determine the efficiency of using the goods themselves. The course of processes in the labor market determines the level of wages. The demand of an enterprise for a productive resource is a derived demand and depends on the consumer’s demand for its final product. Such productive resources as land, labor, and capital are productive and interdependent. The supply of resources in the market changes under the influence of price and non-price factors. In the modern world, the use of more progressive and expensive resources, such as innovative entrepreneurial abilities, digital resources, is becoming more relevant, which causes an increase in the role of intellectual capital in production activities. Ukrainian digital markets are developing extremely rapidly and have great potential to ensure the growth of the country’s economy and competition, including at the international level.